Comparison of LC‐MS/MS vs chemiluminescent microparticle immunoassay in measuring the valproic acid concentration in plasma of epilepsy patients in a new perspective. Issue 1 (15th February 2017) - Wang, Zhipeng; Yun, Yunlei; Xie, Xinfang; You, Chunhua; Miao, Haijun; Zhang, Feng; Gao, Shouhong; Chen, Wansheng
Abstract : Objectives: This study was designed to compare the performance of LC‐MS/MS with chemiluminescent microparticle immunoassay (CMIA) for determination of VPA in epilepsy patients in the perspective of metabolites' hepatotoxicity. Method: Samples were collected and then analyzed using both LC‐MS/MS and CMIA. A LO2 cells (normal human hepatic cells) experiment was carried out to confirm VPA metabolites' hepatotoxicity using AST(Aspertate Aminotransferase, AST), ALT(Alanine aminotransferase, ALT) and LDH(lactate dehydrogenase, LDH) in supernate as index. Results: The regression equation analysis showed as LC‐MS/MS=1.0094 CMIA ‐1.8937, with the concordance correlation coefficient of 0.9700, and the CUSUM test proved no significant deviation from linearity ( P >.05). CMIA compared to LC‐MS/MS gave a positive bias of 1.2 μg/mL. In LO2 experiment, VPA and its metabolites groups showed an obvious increment of AST, ALT, and LDH in supernate. Conclusion: The LC‐MS/MS is largely consistent with the CMIA in analytical time and quantification ability for VPA, but the LC‐MS/MS can simultaneously determinate VPA and its metabolites in plasma, and is also a higher cost‐efficiency method in consideration of toxic metabolites monitoring. The overestimation of VPA by CMIA showed no clinical significance. The metabolites 3‐OH‐VPA and 5‐OH‐VPA damage the LO2 cells and the results presented a statistical significance ( P <.05). It is vital to monitor the metabolites' concentrations for VAP's clinical safety application, and now is the occasion that laboratory and clinic consider the LC‐MS/MS method as a more advantageous alternative to CMIA method in therapeutic monitoring of VPA.